EFFORTS TO IMPROVE STUDENT'S CRITICAL THINKING ABILITY THROUGH THE EXAMPLE NON-EXAMPLE LEARNING MODEL ON THE EYES THEMATIC LESSONS FOR CLASS V ELEMENTARY SCHOOL BADDOKA CITY MAKASSAR - Feni Hardianti; Syarifah Nur Fajrin; Andi Rezky Nurhidayah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This study aims to (1) find out the description of students' critical thinking (2) know the description of the application of the example non example model (3) improve students' critical thinking through the example non example model in thematic subjects. This study uses Classroom Action Research. The research object is the VB class students at Baddoka State Elementary School, Makassar City. Retrieval of data used are observation sheets and tests. The data in this study were analyzed using descriptive qualitative statistical analysis The results of the study show that students' critical thinking skills have increased after using the example non example model in thematic learning. The increase in cycle I was evident in the completeness of student test results, which was 53.6% to 82.1% in cycle II. The percentage of student activity in critical thinking aspects from cycle I to cycle II increased. In aspect (Focus) from 84.4% to 92.8%, aspect (Reason) from 71.3% to 84.4%, aspect (Inference) from 64.2% to 80.9%, aspect (Situation) from 53.5% to 78.5%, aspect (Clarity) from 50.0% to 77.3%. Thus proving that the example non-example learning model can improve students' critical thinking in thematic subjects for class V SD Negeri Baddoka Makassar city.